2019
DOI: 10.1016/j.ymthe.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-drug Antibody Responses Impair Prophylaxis Mediated by AAV-Delivered HIV-1 Broadly Neutralizing Antibodies

Abstract: Adeno-associated virus (AAV) delivery of potent and broadly neutralizing antibodies (bNAbs is a promising approach for the prevention of HIV-1 infection. The immunoglobulin G (IgG)1 subtype is usually selected for this application, because it efficiently mediates antibody effector functions and has a somewhat longer half-life. However, the use of IgG1-Fc has been associated with the generation of anti-drug antibodies (ADAs) that correlate with loss of antibody expression. In contrast, we have shown that expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 56 publications
1
42
1
Order By: Relevance
“…This high level of mutation likely enhances the immunogenicity of these antibodies when delivered to a host other than the one in which those particular sequences originated. Interestingly, when characterizing the humoral responses to the AAV-delivered antibodies we and others have found that the variable regions were predominantly or exclusively targeted (1,11,28,30). We have also reported a highly significant correlation of the magnitude of the host anti-antibody response with the distance from germline of the AAV-delivered antibody: the more mutated, the more immunogenic (28).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…This high level of mutation likely enhances the immunogenicity of these antibodies when delivered to a host other than the one in which those particular sequences originated. Interestingly, when characterizing the humoral responses to the AAV-delivered antibodies we and others have found that the variable regions were predominantly or exclusively targeted (1,11,28,30). We have also reported a highly significant correlation of the magnitude of the host anti-antibody response with the distance from germline of the AAV-delivered antibody: the more mutated, the more immunogenic (28).…”
Section: Introductionmentioning
confidence: 52%
“…For more examples on long-term delivery with AAV of hemophilia factors, please see the following references (61)(62)(63)(64)(65)(66)(67)(68). The long-term delivery described in our report here is significant as the first such report for very long-term delivery of an antibody, particularly given the serious difficulties that have been encountered when AAV has been used to deliver antibodies that are significantly diverged from germ line or contain unusual features (1,14,28,30,31). The findings give hope that long-term delivery of therapeutic antibodies via AAV can be consistently achieved if the ADA problem can be overcome.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The levels of hIgG1 dmAb in the sera declined after d14 to undetectable levels by d35, which is expected in this context in which a xenogeneic human IgG was being expressed in an immune-competent NHP host (29)(30)(31). Accordingly, the decrease in dmAb levels after d14 corresponded with the development of NHP anti-human IgG-dmAb antibodies in the sera (Supplemental Figure 5B and Supplemental Figure 6B).…”
Section: Resultsmentioning
confidence: 56%
“…We have recently published a study that confirms the limitations caused by ADA responses (Gardner et al, 2019b). In our study, we took a different approach, giving four groups of three macaques a combination of rAAV1 vectors encoding either 10-1074 and 3BNC117 or NIH45-46 and PGT121.…”
Section: Adeno-associated Virus Vectors For Delivery Of Hiv-1 Inhibitorsmentioning
confidence: 99%